Secondary battery and electric device

CN119895584APending Publication Date: 2025-04-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380058979.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When charging a high group margin lithium-ion battery, the lattice contraction of the positive active material cannot match the expansion of the negative electrode, causing the electrolyte to be squeezed out, affecting the cycle performance and safety performance of the battery.

Method used

The LiaNibCocM1dM2eOfR′g positive electrode active material system is blended with Li1+xM3nMn1-yA′yP1-zEzO4 to control the battery group margin within the range of 0.9 to 0.95. By adjusting the thickness and number of layers of the positive and negative electrodes, the lattice shrinkage matches the negative electrode. Expansion, improving energy density and cycle performance.

Benefits of technology

It effectively avoids the deterioration of battery performance and safety issues under high group margin, improves the cycle performance and safety of the battery, and takes into account high energy density and long-term performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895584A_ABST
    Figure CN119895584A_ABST
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electric device. The secondary battery comprises a battery shell, a positive plate, a negative plate, a diaphragm and electrolyte, the positive plate, the negative plate, the diaphragm and the electrolyte are arranged in the battery shell, the diaphragm is arranged between the positive plate and the negative plate, the positive plate comprises a positive active material layer, the positive active material layer comprises a first positive active material and a second positive active material, the first positive active material comprises LiaNibCocM1dM2eOfR'g, and a is larger than or equal to 0.75 and smaller than or equal to 1.2, 0lt; blt; 1, 0lt; clt; ct; 1, 0lt; dlt; 0 < = e < = 0.2, 1 < = f < = 2.5, 0 < = g < = 1, f + g < = 3, and M1 is Mn element and / or Al element; the second positive electrode active material comprises Li1 + xM3nMn1-yA'yP1-zEzO4, x is greater than or equal to-0.100 and less than or equal to 0.100, n is greater than or equal to 0 and less than or equal to 1.1, y is greater than or equal to 0.001 and less than or equal to 1, z is greater than or equal to 0 and less than or equal to 0.100, and A'comprises one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge; secondary battery satisfying: # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Secondary battery and electrical device Technical field

[0001] This application belongs to the technical field of batteries. Specifically, it relates to secondary batteries and electrical devices. Background art

[0002] Lithium-ion batteries have the characteristics of being green, environmentally friendly, high-energy, and low-carbon. They are not only used in energy storage power systems such as hydroelectric, thermal, wind, and solar power stations, but also widely used in electric transportation such as electric bicycles, electric motorcycles, and electric vehicles, as well as in multiple fields such as military equipment and aerospace. With the development of society, people's requirements for lithium-ion batteries are also getting higher and higher, such as high energy density, good cycle performance, and safety. Among them, increasing the battery pack margin is one of the common methods to improve the energy density of the battery. However, when the battery pack margin increases, the space available for the expansion of the positive and negative electrode sheets inside the battery decreases accordingly. Therefore, when a high-pack-margin battery is charged, the winding core is likely to severely squeeze out the electrolyte under a large extrusion force, resulting in problems such as lithium plating, which affects the cycle performance and safety performance of the battery.

[0003] Disclosure

[0004] In view of the technical problems existing in the background art, this application provides a secondary battery, aiming to improve the cycle performance and safety performance of high-pack-margin batteries.

[0005] To achieve the above object, the first aspect of this application provides a secondary battery, including: a battery housing and a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte disposed within the battery housing. The separator is provided between the positive electrode sheet and the negative electrode sheet, wherein: the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material.

[0006] The first positive electrode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, etc., and R′ includes one or more elements of N, F, S, Cl, etc.;

[0007] The second positive electrode active material includes Li 1+x M 3nMn 1-y A′ y P 1-z E z O4, wherein -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤1, 0≤z≤0.100, M3 includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, A′ includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge, and E includes one or more elements selected from the group consisting of B, Si, N, S, F, Cl, and Br;

[0008] The secondary battery satisfies:

[0009] Among them, d 正极 is the thickness of the single-layer positive electrode sheet, in mm; d 负极 is the thickness of the negative electrode sheet of a single layer, in mm; d 隔膜 is the thickness of the single-layer diaphragm, in mm; d 壳体 is the inner cavity thickness of the battery shell, in mm; N1 is the number of layers of the positive electrode sheets in the battery shell; N2 is the number of layers of the negative electrode sheets in the battery shell; N3 is the number of layers of the diaphragm in the battery shell.

[0010] Compared with the prior art, the secondary battery of the first aspect of the present application has at least the following beneficial effects: (1) Li a Ni b Co c M 1d M 2e O f R′ g The lattice shrinkage of the positive electrode active material system is small during the charging process. When the battery group margin is high, it cannot match the expansion of the negative electrode during the charging process, which can easily lead to severe squeezing of the electrolyte during the charging process, resulting in lithium plating and other problems that deteriorate the battery performance. a Ni b Co c M 1d M 2e O f R′ g The positive electrode active material Li with large lattice shrinkage during charging is mixed in the positive electrode active material system. 1+x M 3n Mn 1-y A′ y P 1-z E zO4 can effectively improve the lattice shrinkage of the positive electrode and match the expansion of the negative electrode, thereby avoiding the deterioration of battery performance and even safety problems under high group margin as much as possible; (2) The positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g It helps to improve the energy density of the battery by mixing the positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 helps to improve the cycle performance. By flexibly adjusting the relative amount of the two, it is possible to further take into account the high energy density and good cycle performance of the high group margin battery; (3) Controlling the group margin of the battery to the above range can further meet the negative electrode leveling and long-term battery performance while obtaining a high group margin.

[0011] In some embodiments of the present application, the second positive electrode active material includes a positive electrode active material that satisfies at least one of the following conditions: (i) y=1, n=0, and the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' is Fe, or A' is Fe and one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge; (ii) 0.001≤y≤0.500, n=0, and the second positive electrode active material is Li 1+x Mn 1- y A′ y P 1-z E z O4; (iii) 0.001≤y≤0.500, 0.9≤n≤1.1, the second positive electrode active material is Li 1+x M 3n Mn 1- y A′ y P 1-z E z O4.

[0012] In some embodiments of the present application, By making the group margin of the secondary battery further meet the given range, the energy density and good cycle performance of the secondary battery can be further taken into account.

[0013] In some embodiments of the present application, 0.11 mm ≤ d正极 ≤0.16mm, optionally, 0.12mm≤d 正极 ≤0.14mm; 0.15mm≤d 负极 ≤0.20mm, optionally, 0.16mm≤d 负极 By controlling the thickness of the single-layer positive electrode sheet and the single-layer negative electrode sheet within the above-mentioned ranges, the high capacity, cycle performance, and rate performance of the secondary battery can be taken into account at the same time, which is beneficial to improving the discharge current and fast charging performance of the battery.

[0014] In some embodiments of the present application, 0.009 mm ≤ d 隔膜 ≤0.014mm, optionally, 0.0011mm≤d 隔膜 ≤0.012mm. By controlling the thickness of the single-layer separator within the given range, not only can the positive and negative electrodes be prevented from short-circuiting, but also the separator can be easily pierced by burrs, particles, and dendrites, which can cause short circuits. At the same time, it can prevent the separator from being too thick, which will affect the energy density of the battery.

[0015] In some embodiments of the present application, the average lattice volume shrinkage of the positive electrode active material in the fully delithiated state of the positive electrode sheet is no less than 2.7%. By controlling the lattice volume shrinkage of the positive electrode active material within a given range, it is possible to further avoid degradation of battery performance and even the occurrence of safety issues at high group margins, thereby ensuring the long-term performance of the battery.

[0016] In some embodiments of the present application, when the positive electrode sheet is fully delithiated, the lattice volume shrinkage of the second positive electrode active material is 2.7% to 6.9%. By controlling the lattice volume shrinkage of the second positive electrode active material within the given range, the cycle performance and rate performance of the secondary battery can be further balanced.

[0017] In some embodiments of the present application, the average lattice volume shrinkage of the positive electrode active material of the positive electrode sheet is 2.7% to 4.2% when fully delithiated. By controlling the lattice volume shrinkage of the positive electrode active material within the given range, the cycle performance and rate performance of the secondary battery can be further improved.

[0018] In some embodiments of the present application, the active material layer compaction density of the positive electrode sheet is 3.10 g / cm 3 ~3.50g / cm 3 , optional 3.15g / cm 3 ~3.40g / cm 3 , 3.15g / cm2 is optional 3 ~3.35g / cm 3By controlling the compaction density of the active material layer of the positive electrode within a given range, the polarization problem of the electrode can be improved, and the cycle performance and long-term performance of the high group margin battery can be improved.

[0019] In some embodiments of the present application, the compacted density of the active material layer of the negative electrode sheet is 1.6 g / cm 3 ~1.70g / cm 3 , optional 1.64g / cm 3 ~1.69g / cm 3 By controlling the compaction density of the active material layer of the negative electrode sheet within a given range, it is beneficial to further improve the cycle performance and long-term performance of the high group margin battery.

[0020] In some embodiments of the present application, the secondary battery has a liquid filling coefficient of 2.5g / Ah to 3.0g / Ah, optionally 2.62g / Ah to 2.90g / Ah, and more preferably 2.70g / Ah to 2.90g / Ah. By controlling the liquid filling coefficient within the given range, the battery safety can be ensured while also facilitating sufficient electrode wetting and ensuring battery performance.

[0021] In some embodiments of the present application, a first coating layer is provided on the surface of the first positive electrode active material. Optionally, the first coating layer includes one or more elements selected from the group consisting of Ti, Al, B, Nb, Zr, Si, and W. Providing the first coating layer can reduce side reactions between the first positive electrode active material and the electrolyte, improve the structural stability of the positive electrode active material, and enhance cycle performance and safety.

[0022] In some embodiments of the present application, the thickness of the first coating layer is 20 nm to 150 nm.

[0023] In some embodiments of the present application, a second coating layer is provided on the surface of the second positive electrode active material. Optionally, the second coating layer comprises at least one of a pyrophosphate, a phosphate, and carbon. Providing the second coating layer can not only reduce side reactions between the second positive electrode active material and the electrolyte, but also prevent or inhibit the dissolution of transition metals or doping elements, while also improving structural stability, cycling performance, and safety.

[0024] In some embodiments of the present application, the thickness of the second coating layer is 10 nm to 50 nm.

[0025] In some embodiments of the present application, the Dv50 particle size of the first positive electrode active material is 2.1 μm to 6.3 μm, optionally 3.5 μm to 4.9 μm; and / or the Dv50 particle size of the second positive electrode active material is 0.25 μm to 1.49 μm, optionally 0.5 μm to 0.9 μm.

[0026] In some embodiments of the present application, in the second positive electrode active material, E includes one or more elements selected from B, Si, N, and S. By selecting the phosphorus-site doping element E from the given range, it is possible to further help change the difficulty of the Mn-O bond length change, promote lithium ion migration, and improve the rate performance of the secondary battery.

[0027] In some embodiments of the present application, in the second positive electrode active material, A' comprises one or more elements selected from Fe, Ti, V, and Mg. By selecting the manganese-doping element A' from the given range, the structural stability, specific capacity, cycle performance, rate performance, etc. of the secondary battery can be further improved.

[0028] In some embodiments of the present application, the second positive electrode active material includes a positive electrode active material that satisfies at least one of the following conditions: (i) y=1, n=0, and the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' is Fe, or A' includes Fe and one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, Ge; (ii) 0.001≤y≤0.500, n=0, the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4.

[0029] In some embodiments of the present application, the first positive electrode active material and the second positive electrode active material satisfy the following requirements: Among them, n (Ni) is the molar amount of Ni in the positive electrode sheet, in mol; n (A′) is the molar amount of A' in the positive electrode sheet, in mol; n (P) is the molar amount of P in the positive electrode sheet, in mol. and Within the given range, the first positive electrode active material and the second positive electrode active material can have a suitable blending ratio, and the second positive electrode active material can have a suitable manganese site doping ratio and good cycle performance, thereby further enabling the secondary battery to have both higher energy density and better cycle performance.

[0030] In some embodiments of the present application,

[0031] In some embodiments of the present application,

[0032] In some embodiments of the present application, 0.001≤n (Ni) ≤0.0026, optionally, 0.0014≤n (Ni) ≤0.002; 0.00007≤n (A′) ≤0.00075, optionally, 0.0001≤n (A′) ≤0.00032.

[0033] A second aspect of the present application provides an electrical device, which includes: the secondary battery of the first aspect of the present application. DETAILED DESCRIPTION

[0034] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0035] References to "embodiments" in this application mean that a particular feature, structure, or characteristic described in connection with the embodiment may be included in at least one embodiment of the application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described in this application may be combined with other embodiments.

[0036] The "range" disclosed in this application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or the rear upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range that is not clearly stated, and any lower limit can be combined with other lower limits to form a range that is not clearly stated, and similarly any upper limit can be combined with any other upper limit to form a range that is not clearly stated. In addition, each separately disclosed point or single numerical value itself can be combined with any other point or single numerical value as a lower limit or upper limit or with other lower limits or upper limits to form a range that is not clearly stated. For example, if a range of not more than 150 is listed for a particular parameter, it is also contemplated that 10 to 140 and 20 to 120, etc., satisfy a range of not more than 150. Furthermore, if the minimum range values ​​2.1 and 3.5 are listed, and if the maximum range values ​​4.9 and 6.3 are listed, then the following ranges are all contemplated: 2.1-6.3, 2.1-4.9, 3.5-6.3, and 3.5-4.9. In this application, unless otherwise indicated, a numerical range such as "10-50" is an abbreviation for any combination of real numbers between 10 and 50, where 10 and 50 are real numbers. For example, a numerical range of "20-30" indicates that all real numbers between "20-30" are listed herein, and "20-30" is merely an abbreviation for these numerical combinations.

[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0039] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, which means that the method may include steps S1 and S2 performed sequentially, or may include steps S2 and S1 performed sequentially. For example, the method may further include step S3, which means that step S3 may be added to the method in any order, for example, the method may include steps S1, S2, and S3, or may include steps S1, S3, and S2, or may include steps S3, S1, and S2, etc.

[0040] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or comprised, or may mean that only the listed components are included or comprised. Furthermore, as used in this application, the terms "plurality" and "multiple" refer to two or more components.

[0041] Unless otherwise specified, the term "and / or" in this application simply describes an association between related objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. Furthermore, the character " / " in this document generally indicates that the related objects are in an "or" relationship.

[0042] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0043] At present, improving the battery group margin is one of the common methods to improve the battery energy density. However, when the battery shell group margin is improved, the space occupied by the core or laminated unit in the battery increases, that is, the number of cathode and anode sheets contained in the core / laminated unit increases, or the number of core / laminated units increases, and the space inside the battery available for the expansion of the positive and negative sheets is correspondingly reduced. Therefore, when the high group margin battery is charged, the core is severely squeezed out under the action of a large extrusion force, causing problems such as lithium plating. In addition, Li a Ni b Co c M 1d M 2e O f R′ g The lattice shrinkage of the positive electrode active material system is small during the charging process. When the battery group margin is high, it cannot match the expansion of the negative electrode during the charging process. It is also easy to cause the electrolyte to be severely squeezed out during the charging process, resulting in lithium plating and other problems that deteriorate battery performance. Lithium plating will not only reduce battery performance and significantly shorten the cycle life, but also limit the battery capacity. In severe cases, it will cause internal short circuits and may cause catastrophic consequences such as combustion and explosion, resulting in safety problems.

[0044] In view of this, a first aspect of the present application provides a secondary battery, including: a battery case and a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte disposed within the battery case. A separator is provided between the positive electrode sheet and the negative electrode sheet, wherein: the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb; R′ includes one or more elements selected from N, F, S, Cl; the second positive electrode active material includes Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, where -0.100 ≤ x ≤ 0.100, 0 ≤ n ≤ 1.1, 0.001 ≤ y ≤ 1, 0 ≤ z ≤ 0.100, M3 includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, E includes one or more elements selected from B, Si, N, S, F, Cl and Br; the secondary battery satisfies:

[0045]

[0046] where, d 正极 is the thickness of a single-layer positive electrode sheet, in mm; d 负极 is the thickness of a single-layer negative electrode sheet, in mm; d 隔膜 is the thickness of a single-layer separator, in mm; d 壳体 is the inner cavity thickness of the battery case, in mm; N1 is the number of layers of positive electrode sheets in the battery case; N2 is the number of layers of negative electrode sheets in the battery case; N3 is the number of layers of separators in the battery case.

[0047] The inventors found that in Li a Ni b Co c M 1d M 2e O f R′g The positive electrode active material Li with large lattice shrinkage during charging is mixed in the positive electrode active material system. 1+x M 3n Mn 1-y A′ y P 1-z E z O4 can effectively improve the lattice shrinkage of the positive electrode and match the expansion of the negative electrode, thereby avoiding the deterioration of battery performance and even safety problems under high group margin as much as possible. However, the following problems still exist: when the battery is charging, the lithium insertion speed and the internal accumulation state of the active material layer in different areas of the negative electrode sheet are different, which will cause different stresses in different areas of the negative electrode sheet during charging, and eventually cause the sheet to wrinkle (wrinkling will affect the long-term performance of the battery). Under normal circumstances, the negative electrode will be flattened by squeezing the core or laminated unit against the shell during charging. However, when the battery group margin is too low, the use of Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 mixed with Li a Ni b Co c M 1d M 2e O f R′ g When the positive electrode lattice shrinkage is improved, it is easy to cause the core or laminated unit to fail to contact the shell wall during charging, that is, the core or laminated unit cannot be flattened by the external extrusion force, resulting in wrinkles on the negative electrode; when the battery group margin is too high, although Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 mixed with Li a Ni b Co c M 1d M 2e O f R′ g It can improve the lattice shrinkage and reduce the extrusion force on the core during charging. However, as the battery is used for a longer time, side reactions will inevitably occur on the negative electrode surface. These side reactions will increase the thickness of the negative electrode sheet, causing the battery group margin to further increase, exceeding the Li 1+x M 3n Mn 1-y A′ y P 1-z E zThe improvement of O4 mixing will eventually deteriorate the battery performance. It is necessary to control the appropriate group margin to ensure both negative electrode leveling and long-term battery performance. The inventors found that when the battery group margin is controlled to meet the range of the above formula (0.9 to 0.95), while using Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 mixed with Li a Ni b Co c M 1d M 2e O f R′ g When the positive electrode lattice shrinkage is improved, it is not only beneficial to the leveling of the negative electrode, but also can effectively match the expansion of the negative electrode, thereby avoiding the deterioration of battery performance and even safety problems under high group margin as much as possible, that is, it can further meet the leveling of the negative electrode and the long-term performance of the battery while obtaining a high group margin; In addition, the positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g It helps to improve the energy density of the battery by mixing the positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 helps improve cycle performance, and by flexibly adjusting the relative amounts of the two, it is possible to further balance the high energy density and good cycle performance of high-group-margin batteries. Overall, this secondary battery not only facilitates negative electrode leveling and long-term battery performance, but also further balances the high energy density and good cycle performance of high-group-margin batteries, thereby improving the service life and safety of the secondary battery.

[0048] Furthermore, after in-depth research, the inventors have discovered that, in addition to meeting the aforementioned conditions, the secondary battery of the present application can further improve its performance by controlling the selection of the positive electrode active material, the thickness of the electrode and separator, the lattice shrinkage of the positive electrode active material, the compaction density of the electrode active material layer, and the injection coefficient. That is, in addition to meeting the aforementioned conditions, one or more of the following conditions can also be optionally met.

[0049] In some embodiments of the present application, the first positive electrode active material may be partially Li a Ni b Co c M 1d M2e O f R′ g may also be all Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ includes one or more elements of N, F, S, Cl. Optionally, 0.5 ≤ b < 1, 0 < c ≤ 0.5, 0 < d ≤ 0.5, so that the positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g meets the above given range conditions, which is more conducive to making the secondary battery have both a high energy density, good cycle performance and a long cycle life. In the positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g , taking the nickel-cobalt-manganese ternary positive electrode active material (i.e., NCM) system as an example, increasing the nickel content can increase the volumetric energy density of the positive electrode material; increasing the manganese content can reduce the material cost, improve the safety and structural stability of the material, but too high manganese content will damage the layered structure of the material and reduce the specific capacity of the material; cobalt can stabilize the layered structure of the material and improve the cycle and rate performance of the material, but too high cobalt content will lead to a decrease in the actual capacity. By making the nickel-cobalt-manganese content meet the above given range conditions, the secondary battery can have a high energy density, good rate performance and cycle performance. Optionally, M1 can be the Mn element, and the first positive electrode active material can be the positive electrode active material of the NCM system. At this time, its general formula can be Li a Ni b Co c Mn d M 2e O f R′ g , for example, it can be a nickel-cobalt-manganese ternary layered positive electrode active material.

[0050] In some embodiments of the present application, the second positive electrode active material may be partially Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, or all Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, wherein, -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤1, 0≤z≤0.100, M3 includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, and E includes one or more elements selected from B, Si, N, S, F, Cl and Br. Doping at least one of the lithium site, manganese site and phosphorus site can help improve the performance of the positive electrode active material, for example, it can improve the interface performance, reduce the interface side reaction with the electrolyte, reduce the concentration of antisite defects, improve the kinetic performance and gram capacity of the material, etc. At the same time, by regulating the doping element at the manganese site, the particle morphology can also be improved and the compaction density can be increased. Specifically, While a higher lattice shrinkage rate is more conducive to matching the volume expansion of the negative electrode during charging, excessive lattice shrinkage of the positive electrode material can hinder lithium ion transport. Selecting the aforementioned elements for the manganese-doped element A' helps minimize the lattice change rate during lithium insertion and extraction, improving the structural stability of the positive electrode material, reducing the dissolution of the manganese-doped element and lowering the oxygen activity on the particle surface. This, in turn, increases the specific capacity of the material and reduces interfacial side reactions with the electrolyte during use, thereby enhancing the material's cycling performance. Selecting the aforementioned elements for the phosphorus-doped element E also helps modify the ease of Mn-O bond length change, thereby improving electronic conductivity and lowering the lithium ion migration barrier, promoting lithium ion migration and enhancing the rate performance of the secondary battery. Similarly, selecting the aforementioned elements for the lithium-doped element M3 also helps improve the lattice change rate and maintain the material's capacity. If the value of x is too small, the lithium content of the entire core system will be reduced, affecting the specific capacity of the material. The value of y limits the total amount of all doping elements, affecting the manganese content in the system and the material's voltage plateau. The E element is doped in the position of phosphorus. Since the PO tetrahedron is relatively stable, a large z value will affect the stability of the material. When x, y and z are selected from the above ranges, the positive electrode active material can have better performance. In addition, the selection of the above doping elements and the values ​​of x, n, y and z can also make Li 1+x M 3n Mn 1-yA′ y P 1-z E z O4 maintains electrical neutrality, and maintaining electrical neutrality can ensure that the defects and impurities in the positive electrode active material are as few as possible. Taking the positive electrode active material of the lithium manganese phosphate system as an example, if there is an excess of transition metal (such as manganese), since the structure of the material system itself is relatively stable, the excess transition metal is likely to precipitate in the form of a single substance, or form an impurity phase inside the lattice. Maintaining electrical neutrality can minimize such impurities. In addition, ensuring the electrical neutrality of the system can also produce lithium vacancies in the positive electrode active material in some cases, thereby making the kinetic performance of the positive electrode active material better. Compared with existing materials such as lithium manganese phosphate, lithium iron phosphate, and lithium manganese iron phosphate that can be applied to high voltage systems, it is more conducive to obtaining better cycle performance and high temperature stability, as well as larger gram capacity and larger compaction density. It can be understood that in the "manganese position" doping described in this application, the manganese position only represents the positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z The position of the manganese element or A' element in the O4 lattice does not necessarily mean that there is a manganese element in the manganese position. The manganese element on the manganese position can be partially or completely replaced by the A' element. For example, when the y value is 1, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 does not contain manganese. For example, in this case, the manganese position may include iron or iron and other doping elements.

[0051] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z In O4, E may include one or more elements selected from B, Si, N and S. By selecting the phosphorus-doped element E from a given range, it can further help to change the difficulty of changing the Mn-O bond length, thereby improving electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery.

[0052] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E zIn O4, A' can include one or more elements selected from Fe, Ti, V, and Mg. Alternatively, A' can be Fe; further alternatively, A' can be at least two elements selected from Fe, Ti, V, and Mg; and further alternatively, A' can be Fe and one or more elements selected from Ti, V, and Mg. By selecting the manganese-doped element A' within the given range, the structural stability, specific capacity, cycle performance, and rate capability of the secondary battery can be further improved.

[0053] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z In O4, doping can be performed simultaneously at the manganese and phosphorus sites. This not only effectively reduces the dissolution of manganese elements, thereby reducing the number of manganese ions migrating to the negative electrode, reducing the amount of electrolyte consumed due to SEI film decomposition, and improving the cycle performance and safety performance of the secondary battery, but also promotes the adjustment of Mn-O bonds, lowers the lithium ion migration barrier, promotes lithium ion migration, and improves the rate performance of the secondary battery. Alternatively, doping can be performed simultaneously at the lithium, manganese, and phosphorus sites, thereby further achieving significantly improved rate performance, improved cycle performance, and / or high-temperature stability.

[0054] In some embodiments of the present application, the second positive electrode active material may include a lithium manganese phosphate system, a lithium iron phosphate system, a lithium manganese iron phosphate system, and the like, all of which conform to the above general formula Li 1+x M 3n Mn 1-y A′ y P 1-z E z One or more of the positive electrode active materials of O4, for example, the second positive electrode active material may include a positive electrode active material that meets at least one of the following three conditions: (i) y = 1, n = 0, in which case the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' can be Fe, or A' can be Fe and include one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge, i.e., the second positive electrode active material can include lithium iron phosphate or lithium iron phosphate doped with at least one of an iron site (same as a manganese site) and a phosphorus site. (ii) 0.001≤y≤0.500, n=0, in which case the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E zO4, that is, lithium manganese phosphate or lithium manganese phosphate doped with at least one of the lithium, manganese and phosphorus positions. In this application, the modification of lithium manganese phosphate can achieve significantly reduced dissolution of manganese elements and reduced lattice change rate. Its use in secondary batteries is more conducive to improving the battery's cycle performance, rate performance, safety performance and capacity. For example, by doping specific elements in specific amounts at the lithium, manganese and phosphorus positions of the compound LiMnPO4, improved rate performance can be obtained, while reducing the dissolution of Mn and the doping elements at the Mn position, obtaining improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the positive electrode active material can also be improved. As a specific example, Li 1+x Mn 1-y A′ y P 1-z E z O4 may include Li 1+x Mn 1- y Fe y P 1-z E z O4, compared with lithium iron phosphate, lithium manganese iron phosphate has a higher voltage platform and a higher energy density when the specific capacity is the same. (iii) 0.001≤y≤0.500, 0.9≤n≤1.1, the second positive electrode active material is Li 1+x M 3n Mn 1- y A′ y P 1-z E z O4. For the second positive electrode active material of the lithium manganese phosphate system, considering that the value of y will limit the total amount of all doping elements, if y is too small, that is, the doping amount is too little, the doping elements will not play a role. If y exceeds 0.5, it will lead to a low Mn content in the system, affecting the voltage platform of the material. The value range of y can be selected from 0.001 to 0.500, and then from 0.25 to 0.5. It should be noted that the chemical formula Li involved in the above three conditions 1+x A′P 1-z E z O4、Li 1+x Mn 1-y A′ y P 1- z E z O4 and Li 1+x M 3n Mn 1-y A′ y P 1-z E z In O4, the stoichiometric numbers of elements at the same site can be the same or different, but they all satisfy the chemical formula Li1+x M 3n Mn 1-y A′ y P 1-z E z The numerical range defined for the stoichiometric number of each element in O4.

[0055] As a specific example, the second positive electrode active material may include a positive electrode active material that satisfies at least one of the following two conditions: (i) y=1, n=0, and the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' is Fe, or A' includes Fe and one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, Ge; (ii) 0.001≤y≤0.500, n=0, the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1- z E z Alternatively, the second positive electrode active material may include only the chemical formula Li 1+x A′P 1-z E z O4 and / or chemical formula Li 1+x Mn 1-y A′ y P 1-z E z O4 positive electrode active material, in the two chemical formulas, the values ​​of x and z are independent of each other, but both satisfy the chemical formula Li 1+x M 3n Mn 1-y A′ y P 1-z E z The numerical ranges defined for the stoichiometric numbers of x and z in O4.

[0056] In this application, the chemical formula of the first positive electrode active material is Li a Ni b Co c M 1d M 2e O f R′ g and the chemical formula of the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E zO4, unless otherwise specified, when a doping site has two or more elements, the numerical range of the stoichiometric number of the elements of the corresponding doping site in the chemical formula is not only limited to the stoichiometric number of each element as the site, but also limited to the sum of the stoichiometric numbers of the elements as the site. For example, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z Taking the chemical formula of O4 as an example, when A1′ is two or more elements A1′, A2′…A n ', A1', A2'...A n 'The respective stoichiometric numbers y1, y2...y n Each of them must fall within the numerical range of y specified in this application, and y1, y2...y n Similarly, for the case where M3 or E is two or more elements, the numerical ranges of the stoichiometric numbers of M3 and E defined in this application also have the above meanings.

[0057] In some embodiments of the present application, the following conditions are also met: That is, the group margin of the secondary battery can be 0.91 to 0.94, for example, it can be 0.915, 0.92, 0.925, 0.93, 0.935, etc., or it can be a range composed of any of the above values. For the secondary battery of the present application, considering that when the battery group margin is too low, it is not conducive to the contact between the battery core or laminated unit and the battery shell, and thus it cannot be flattened by the external extrusion force, resulting in wrinkling of the negative electrode, and when the battery group margin is too high, as the battery is used for a longer time, side reactions will inevitably occur on the surface of the negative electrode. These side reactions will increase the thickness of the negative electrode sheet, causing the battery group margin to further increase, exceeding the Li 1+x M 3n Mn 1-y A′ y P 1-z E z The improvement of O4 mixing ultimately deteriorates battery performance, and the battery group margin can be further controlled within the range of 0.91 to 0.94. This can further ensure the negative electrode leveling and long-term battery performance of the secondary battery, and is conducive to further balancing the energy density and good cycle performance of the secondary battery. Among them, this group margin can be achieved by controlling the thickness and number of layers of the positive electrode sheet, negative electrode sheet, and separator in the battery casing, as well as the thickness of the inner cavity of the battery casing.

[0058] In some embodiments of the present application, in the secondary battery, the thickness d of the single-layer positive electrode sheet is 正极 Meet the following conditions: 0.11mm≤d正极 ≤0.16mm, for example d 正极 It can be 0.115mm, 0.12mm, 0.125mm, 0.13mm, 0.135mm, 0.14mm, 0.145mm, 0.15mm or 0.155mm, or any range thereof. 负极 Meet the following conditions: 0.15mm≤d 负极 ≤0.20mm, for example d 负 极 It can be 0.155mm, 0.16mm, 0.165mm, 0.17mm, 0.175mm, 0.18mm, 0.185mm, 0.19mm or 0.195mm, etc., or it can be a range composed of any of the above values. Among them, if the thickness of the positive electrode sheet / negative electrode sheet is too small, it means that the active material coating on the electrode sheet is too thin or the compaction density is too large. The former will affect the energy density, and the latter will affect the infiltration of the electrolyte into the electrode sheet, deteriorating the cycle performance. If the thickness is too large, it means that the active material coating is too thick or the compaction density is too small. The former will increase the polarization of the electrode sheet and deteriorate the battery performance, and the latter will increase the contact resistance between particles in the electrode sheet and deteriorate the battery performance. In this application, by controlling the thickness of the single-layer positive electrode sheet and the single-layer negative electrode sheet to be within the above-mentioned ranges, the high capacity, cycle performance and rate performance of the secondary battery can be taken into account at the same time, which is beneficial to improving the discharge current and fast charging performance of the battery. Optionally, 0.12mm≤d 正极 ≤0.14mm, and optionally, 0.16mm≤d 负极 ≤0.18mm, and controlling the thickness of the single-layer positive electrode sheet and the single-layer negative electrode sheet within the given range can further take into account the high capacity, cycle performance, and rate performance of the secondary battery. It should be noted that the measurement method of the thickness of the positive electrode sheet and the thickness of the negative electrode sheet is not particularly limited, and those skilled in the art can flexibly select according to actual needs. Specifically, conventional testing methods in the field can be used, such as using a lithium battery electrode sheet thickness measuring instrument to detect the thickness of the secondary battery electrode sheet.

[0059] In some embodiments of the present application, in the secondary battery, the thickness d of the single-layer separator is 隔膜 Meet the following conditions: 0.009mm≤d 隔膜 ≤0.014mm, for example d 隔膜It can be 0.01mm, 0.011mm, 0.012mm, 0.013mm, etc., or it can be a range composed of any of the above values, wherein, if the thickness of the diaphragm is too large, it will increase the difficulty of battery polarization and electrolyte infiltration, and deteriorate the battery energy density. If the thickness of the diaphragm is too small, it will affect the battery safety performance. In this application, controlling the thickness of the single-layer diaphragm within the given range can not only effectively ensure the insulation between the positive and negative electrodes, and prevent the positive and negative electrodes from short-circuiting, but also make the diaphragm have certain tensile resistance, tear resistance and puncture resistance, and prevent the diaphragm from being easily pierced by burrs, particles, and dendrites and causing short circuits. At the same time, controlling the thickness of the single-layer diaphragm within the given range can also avoid the diaphragm thickness being too large to affect the energy density of the battery. Optionally, 0.0011mm≤d 隔膜 ≤0.012mm, thereby effectively preventing short circuits caused by contact between the positive and negative electrodes and the separator being easily pierced by burrs, particles, and dendrites, and further reducing the negative impact of the separator on the energy density of the secondary battery. The separator thickness can also be tested using conventional methods in the field, such as GB / T 6672-2001.

[0060] In some embodiments of the present application, when the positive electrode sheet is in a fully delithiated state, the average lattice volume shrinkage rate of the positive electrode active material may be no less than 2.7%, for example, it may be 2.8%, 3%, 3.2%, 3.5%, 4.0%, 2.7-7%, etc., or it may be a range composed of any of the above values. The lattice volume shrinkage is related to the lithiation state of the positive electrode material, that is, the delithiation state of the positive electrode material (the positive electrode material is initially in a fully lithium-intercalated state. As the charging process proceeds, lithium is extracted from the positive electrode material, reaches the negative electrode, and is then re-intercalated). As charging proceeds, the lithium content in the positive electrode material decreases, accompanied by lattice volume shrinkage (after delithiation, the valence state of some elements participating in the electrochemical reaction in the positive electrode material will increase accordingly. At this time, its ionic radius decreases, which is manifested as lattice volume shrinkage on a macro scale). The degree of lattice volume shrinkage is different under different delithiated states. In this application, the fully delithiated state is taken as an example (that is, from the fully lithium-intercalated state to the fully delithiated state). The Li a Ni b Co c M 1d M 2e O f R′ g The lattice volume shrinkage is generally no more than 2.7%, while the doped Li 1+x M 3n Mn 1-y A′ y P 1-z E zThe lattice volume shrinkage rate of O4 in the fully delithiated state is relatively high. After the first positive electrode active material and the second positive electrode active material are blended, by controlling the lattice volume shrinkage rate of the blended positive electrode active material in the fully delithiated state within a given range, the expansion of the negative electrode during the charging process can be further matched, thereby avoiding the deterioration of battery performance and even the occurrence of safety problems under high group margin as much as possible, which is conducive to meeting the long-term performance of the battery. It should be noted that in this application, the average lattice volume shrinkage rate of the positive electrode active material refers to the lattice volume shrinkage rate of the composite positive electrode active material obtained by blending the first positive electrode active material and the second positive electrode active material in the fully delithiated state. In view of the different lattice volume shrinkage rates of the first positive electrode active material and the second positive electrode active material in the fully delithiated state, the average lattice volume shrinkage rate is used here to refer to the lattice shrinkage rate of the blended composite positive electrode active material in the fully delithiated state.

[0061] In some embodiments of the present application, when the positive electrode sheet is in a fully delithiated state, the lattice volume shrinkage rate of the second positive electrode active material can be 2.7% to 6.9%, for example, 2.9%, 3.3%, 3.6%, 4.1%, 4.5%, 4.8%, 5.2%, 5.6%, 6.0%, 6.4%, 6.8%, etc., or can be a range composed of any of the above values. Among them, although a higher lattice shrinkage rate is more conducive to matching the volume expansion of the negative electrode during charging, if the lattice shrinkage rate of the positive electrode material is too high, it is not conducive to the transmission of lithium ions. By further controlling the lattice volume shrinkage rate of the second positive electrode active material in a fully delithiated state within a given range, the positive electrode active material obtained by blending the second positive electrode material with the first positive electrode material can have a more suitable volume shrinkage rate, thereby better matching the volume expansion of the negative electrode during charging, promoting the transmission of lithium ions, making the lithium ion migration ability stronger, and further taking into account the cycle performance and rate performance of the secondary battery. Furthermore, when the positive electrode sheet is in a fully delithiated state, the average lattice volume shrinkage rate of the positive electrode active material can be 2.7% to 4.2%, that is, the average lattice volume shrinkage rate of the positive electrode active material obtained by mixing the first positive electrode material and the second positive electrode material in a fully delithiated state can be 2.7% to 4.2%. This can not only better match the volume expansion of the negative electrode during the charging process, but also further ensure that the lithium ions have better migration ability, which is more conducive to improving the cycle performance and rate performance of the secondary battery.

[0062] In the present application, the lattice volume shrinkage rate of the positive electrode active material can be measured by methods known in the art, for example, it can be measured by methods such as X-ray diffraction (XRD). As a specific example, XRD testing can be performed on the positive electrode active material in different delithiation states (points can be selected based on the charging curve of the button battery of the positive electrode material. It is recommended to select one point for every 5% SOC, SOC = capacity when charged to a certain voltage / total charging capacity). The XRD test conditions are 12 degrees to 40 degrees, and the scanning rate is 0.02 degrees / min. The test data is processed using Jade software to obtain the lattice parameters a / b / c / β of the positive electrode material in this state. The lattice volume in this state is calculated according to the formula V = abc×sinβ. By analogy, the lattice volume shrinkage rate can be calculated by obtaining the lattice volume of the positive electrode material in different delithiation states. The lattice volume shrinkage rate in the fully delithiation state = (lattice volume (fully delithiation state) - lattice volume (not delithiation state)) / lattice volume (not delithiation state) × 100%. Among them, the method for obtaining positive electrode active materials in different delithiation states can be as follows: assemble the positive electrode active materials into a button battery, charge the button battery to a selected voltage according to the method described above, and then disassemble the button battery in a glove box, take out the positive electrode sheet, soak it in DMC solution for 6 hours, and then rinse it repeatedly with DMC solution 2 to 3 times, and then dry the electrode sheet.

[0063] In some embodiments of the present application, the active material layer compaction density of the positive electrode sheet can be 3.10 g / cm 3 ~3.50g / cm 3 , for example, it can be 3.15g / cm 3 、3.20g / cm 3 、3.25g / cm 3 、3.30g / cm 3 、3.35g / cm 3 、3.40g / cm 3 、3.45g / cm 3etc., or can be a range consisting of any of the above values. Among them, the compacted density of the active material layer of the positive electrode sheet can be measured according to GB / T 24533-2009. If the compacted density of the positive electrode active material layer in the positive electrode sheet is too small, it is easy to cause loose contact between the particles inside the electrode sheet and increase the contact resistance. In addition, the positive electrode sheet with too small compacted density of the positive electrode active material layer is thicker and it is difficult to meet the high group margin design requirements; and if the compacted density of the positive electrode active material layer of the positive electrode sheet is too large, it will lead to two problems. First, it is easy to cause some particles inside the electrode sheet to break / produce cracks after cold pressing. The broken particles / cracks are easy to react with the electrolyte to cause battery performance degradation. When the battery is cycled, due to the high pressure inside the electrode sheet, the mutual squeezing between the particles is also easy to cause particle breakage; second, the porosity of the electrode sheet decreases, the difficulty of electrolyte infiltration increases, and thus it is easy to cause battery performance degradation. In this application, by controlling the compacted density of the active material layer of the positive electrode sheet within the given range, it is more conducive to improving the polarization problem of the electrode sheet and improving the cycle performance and long-term performance of the high group margin battery. Optionally, the active material layer compaction density of the positive electrode sheet can be 3.15 g / cm 3 ~3.40g / cm 3 , and the optional one can be 3.15g / cm 3 ~3.35g / cm 3 , which can further help improve the cycle performance and long-term performance of high group margin batteries.

[0064] In some embodiments of the present application, the compacted density of the active material layer of the negative electrode sheet can be 1.6 g / cm 3 ~1.70g / cm 3 , for example, it can be 1.62 g / cm 3 , 1.64g / cm 3 , 1.66g / cm 3 , 1.68 / cm 3 Etc., or it can be a range consisting of any of the above values. Among them, the compaction density of the active material layer of the negative electrode sheet can be measured according to GB / T 24533-2009. If the compaction density of the negative electrode active material layer in the negative electrode sheet is too small, it will also lead to loose contact between the particles inside the electrode sheet and increase the contact resistance. At the same time, it is not conducive to meeting the requirements of high group margin design. If the compaction density of the negative electrode active material layer is too large, it will easily lead to battery performance degradation. In this application, by controlling the compaction density of the active material layer of the negative electrode sheet within the given range, it is not only beneficial to improve the negative electrode performance, but also more conducive to achieving the matching of the lattice volume shrinkage rate of the positive electrode active material and the volume expansion of the negative electrode during charging, which is beneficial to further improve the cycle performance and long-term use performance of the high group margin battery. Optionally, the compaction density of the active material layer of the negative electrode sheet can be 1.64g / cm 3 ~1.69g / cm 3, which can further help improve the cycle performance and long-term performance of high group margin batteries.

[0065] In some embodiments of the present application, the filling coefficient of the secondary battery can be 2.5g / Ah to 3.0g / Ah, for example, 2.6g / Ah, 2.65g / Ah, 2.7g / Ah, 2.75g / Ah, 2.8g / Ah, 2.85g / Ah, 2.9g / Ah, 2.95g / Ah, etc., or can be a range composed of any of the above values. The inventors found that when the secondary battery group margin is high and the positive electrode compaction density is large, the corresponding electrolyte infiltration difficulty is also greater. If the filling coefficient is too low, the amount of electrolyte is small, it is difficult to meet the infiltration requirements of the electrode, and it is easy to cause rapid deterioration of battery performance; if the filling coefficient is too high, the internal free space of the battery will be further reduced, and the battery will produce gas inside during use. The reduction of the internal free space will cause the internal pressure of the battery to increase, affecting the safety of the battery. In this application, by controlling the filling coefficient within the above-mentioned range, it is possible to ensure the safety of the battery and facilitate sufficient infiltration of the electrode to ensure battery performance. Optionally, the filling coefficient of the secondary battery may be 2.62 g / Ah to 2.90 g / Ah, and further may be 2.70 g / Ah to 2.90 g / Ah, thereby further taking into account both battery safety and battery performance.

[0066] In some embodiments of the present application, a first coating layer may be provided on the surface of the first positive electrode active material. Optionally, the first coating layer may include one or more elements selected from the group consisting of Ti, Al, B, Nb, Zr, Si, and W. Providing a coating layer on the surface of the positive electrode active material can not only prevent the positive electrode active material from contacting the electrolyte, thereby reducing side reactions between the positive electrode active material and the electrolyte, but also improve the stability of the structure of the positive electrode active material, thereby improving the cycle stability and safety of the material. In addition, the above elements in the first coating layer can be provided in the form of oxides (such as Al2O3, ZrO2, TiO2, Nb2O3, etc.) or in the form of lithium compounds, etc., so that the first coating layer contains the above-mentioned element range, which can improve the surface ionic conductivity of the material, improve the material rate performance and specific capacity, stabilize the material structure, avoid direct contact between the material and the electrolyte, and improve the cycle performance.

[0067] In some embodiments of the present application, the thickness of the first coating layer can be 20nm to 150nm, for example, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, etc., or can be a range composed of any of the above values. The inventors found that when the thickness of the first coating layer is too thin, the possibility of its cracking / deep damage during the use of the positive electrode active material will increase, resulting in a significant reduction in the effect of improving and protecting the performance of the first positive electrode active material; when the thickness of the first coating layer is too thick, lithium ions require a longer transmission path to reach the active material system from the electrolyte, which has a greater impact on the performance of the active material. In addition, when the coating layer is sintered, the coating material will react with the lithium in the internal material, resulting in a reduction in the available active lithium in the material and a corresponding reduction in the specific capacity of the material. In this application, by controlling the thickness of the first coating layer within the above-mentioned range, the above problems can be effectively avoided or reduced, the rate performance of the first positive electrode active material can be effectively improved, and the surface structure of the material can be stabilized.

[0068] In some embodiments of the present application, the Dv50 particle size of the first positive electrode active material is 2.1μm to 6.3μm, for example, it can be 2.4μm, 2.7μm, 3.0μm, 3.3μm, 3.6μm, 3.9μm, 4.2μm, 4.5μm, 4.8μm, 5.1μm, 5.4μm, 5.7μm, 6.0μm, etc., or it can be a range composed of any of the above values. The Dv50 of the first positive electrode active material refers to the particle size corresponding to when the cumulative volume distribution percentage of the first positive electrode active material reaches 50%. In the present application, the Dv50 particle size of the first positive electrode active material can be measured by laser diffraction particle size analysis, for example, with reference to standard GB / T19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000) for measurement. In this application, by controlling the Dv50 particle size of the first positive electrode active material within the given range, it is not only beneficial to prevent it from breaking or pulverizing during the charge and discharge process, thereby reducing the capacity loss of the secondary battery, but also can shorten the diffusion path of active ions and increase the conduction rate of electrons, which is beneficial to improving the cycle performance of the secondary battery; at the same time, it can also make the active material have suitable active sites, reduce or avoid the fact that there are more active sites when the particle size is too small, which increases the side reactions of the material during the cycle, and has a greater negative impact on the cycle performance, and that there are fewer active sites when the particle size is too large, which has a greater negative impact on the power performance. In addition, based on the thickness of the first coating layer, controlling the Dv50 particle size of the first positive electrode active material within the given range can further ensure that the secondary battery has a higher energy density. Optionally, the Dv50 particle size of the first positive electrode active material can be 3.5μm to 4.9μm, which can further take into account the high energy density and good cycle performance of the secondary battery.

[0069] In some embodiments of the present application, a second coating layer may be provided on the surface of the second positive electrode active material. The provision of the second coating layer can not only prevent the second positive electrode active material from contacting the electrolyte, thereby reducing the side reaction between the second positive electrode active material and the electrolyte, but also prevent or inhibit the dissolution of transition metals or doping elements in the second positive electrode active material, while improving its structural stability, thereby improving the cycle stability and safety of the positive electrode active material. Optionally, the second coating layer may include at least one of pyrophosphate, phosphate and carbon. Among them, metal ions are difficult to migrate in pyrophosphate, and selecting pyrophosphate as the coating layer material can effectively isolate the metal ions doped in the positive electrode material from the electrolyte; further, the pyrophosphate can be selected as a crystalline pyrophosphate, which has a stable structure and can be used as a coating layer material to effectively inhibit the dissolution of transition metals in the active material and improve the cycle performance. Phosphate coating can improve the ion transport properties of the positive electrode material, which is beneficial for promoting the transmission of lithium ions. Furthermore, the phosphate can be a crystalline phosphate. Crystalline phosphate and crystalline pyrophosphate have a high lattice matching degree, good stability, and excellent lithium ion conductivity. Using them to coat the second positive electrode active material can improve the stability of the positive electrode active material and effectively reduce the interfacial side reactions of the electrolyte, thereby improving the high-temperature cycling and storage performance of the battery. Carbon coating can effectively improve the conductivity and desolvation ability of the positive electrode active material. Carbon materials have good electronic conductivity. When used in secondary batteries, electrochemical reactions occur, which require the participation of electrons. In order to increase electron transmission between particles and electron transmission at different positions of particles, carbon with excellent conductive properties can be used to coat the positive electrode active material. It can be understood that when the second coating layer includes pyrophosphate, phosphate and carbon at the same time, the pyrophosphate, phosphate and carbon can be located in the same coating layer or in at least two sub-coating layers. For example, a pyrophosphate coating layer, a phosphate coating layer and a carbon coating layer can be formed in sequence on the surface of the second positive electrode active material, or a phosphate coating layer, a pyrophosphate coating layer and a carbon coating layer can be formed in sequence on the surface of the second positive electrode active material, or a composite coating layer of pyrophosphate and phosphate can be first formed on the surface of the second positive electrode active material, and then a carbon coating layer can be formed on the surface of the composite coating layer.

[0070] In some embodiments of the present application, the thickness of the second coating layer may be 10 nm to 50 nm. For example, it may be 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, etc., or may be a range consisting of any of the above values. Controlling the thickness of the second coating layer within the given range can not only effectively hinder the dissolution of the transition metal or doping element in the second positive electrode active material, but also avoid the coating thickness being too large to affect the migration of lithium ions and affect the battery energy density, thereby further improving the battery's kinetic performance, cycle performance and safety without sacrificing the gram capacity of the second positive electrode active material.

[0071] As a specific example, the second coating layer may include a first sub-coating layer, a second sub-coating layer, and a third sub-coating layer. The first sub-coating layer may coat the second positive electrode active material and include crystalline pyrophosphate. The second sub-coating layer may include crystalline phosphate and coat the first sub-coating layer. The third sub-coating layer may be carbon and coat the second sub-coating layer. Pyrophosphate as the first sub-coating layer can effectively isolate the metal ions doped in the second positive electrode active material from the electrolyte. The crystalline pyrophosphate coating can effectively inhibit the dissolution of transition metals in the second positive electrode active material, thereby improving the cycle performance. The crystalline phosphate as the second sub-coating layer has a high lattice match with the crystalline pyrophosphate in the first sub-coating layer, is more stable than pyrophosphate, and has excellent lithium ion conductivity, which is beneficial for improving the stability of the positive electrode active material and reducing the interfacial side reactions between the positive electrode active material and the electrolyte. The third sub-coating layer can enhance electron transport between particles, improve the electronic conductivity of the positive electrode active material, and effectively improve the conductive properties and desolvation ability of the positive electrode active material. Further, the thickness of the first sub-coating layer can be 1nm to 10nm, such as 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, etc., or within any range of the above-mentioned arbitrary values. When the thickness of the first sub-coating layer is within the given range, it can avoid the adverse effects on the kinetic properties of the positive electrode active material that may be caused when it is too thick, and can avoid the problem that it may not effectively hinder the migration of transition metal ions when it is too thin; the thickness of the second sub-coating layer can be 2nm to 15nm, such as 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, etc., or within any range of the above-mentioned arbitrary values. The thickness of the second sub-coating layer is too large and may cause Affects the overall platform voltage of the positive electrode active material. When the thickness of the second sub-coating layer is within the given range, its surface structure is stable, the side reaction with the electrolyte is small, and the interface side reaction can be effectively reduced, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery; the thickness of the third sub-coating layer can be 2nm to 25nm, such as 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, etc., or within any range of any of the above values. When the thickness of the third sub-coating layer is within the given range, it can improve the electrical conductivity of the positive electrode active material and the compaction density of the positive electrode sheet, while avoiding the problem of the sub-coating layer containing amorphous carbon affecting the compaction density of the sheet due to excessive coating thickness.

[0072] Among them, in this application, the thickness test of each coating layer can be carried out by FIB, and the specific method may include the following steps: randomly selecting a single particle from the positive electrode active material powder to be tested, cutting a thin slice with a thickness of about 100 nm from the middle position or near the middle position of the selected particle, and then performing TEM testing on the thin slice to measure the thickness of the coating layer, measuring 3 to 5 positions, and taking the average value.

[0073] In some embodiments of the present application, the Dv50 particle size of the second positive electrode active material may be 0.25 μm to 1.49 μm, for example, it may be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, etc., or it may be a range composed of any of the above values. The Dv50 of the second positive electrode active material refers to the particle size corresponding to when the cumulative volume distribution percentage of the second positive electrode active material reaches 50%. In the present application, the Dv50 particle size of the second positive electrode active material can be measured by laser diffraction particle size analysis, for example, with reference to standard GB / T19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000) for measurement. In the present application, by controlling the Dv50 particle size of the second positive electrode active material within the given range, it is not only beneficial to prevent it from breaking or pulverizing during the charge and discharge process, thereby reducing the capacity loss of the secondary battery, but also can shorten the diffusion path of active ions and increase the conduction rate of electrons, which is beneficial to improving the cycle performance of the secondary battery; at the same time, it can also enable the active material to have suitable active sites, while taking into account both cycle performance and power performance; and, controlling the Dv50 particle size of the second positive electrode active material within the given range is also beneficial to matching the Dv50 particle size range of the first positive electrode active material to achieve the expected compaction density, avoiding large gaps between the positive electrode active material particles; in addition, based on the thickness of the second coating layer, controlling the Dv50 particle size of the second positive electrode active material within the given range can further ensure that the secondary battery has a higher energy density, and reduce the lattice change rate of the second positive electrode active material and the dissolution of transition metals or doping elements, thereby improving the high-temperature cycle stability and high-temperature storage performance of the secondary battery. Optionally, the Dv50 particle size of the second positive electrode active material may be 0.5 μm to 0.9 μm, thereby further taking into account both high energy density and good cycle performance of the secondary battery.

[0074] In some embodiments of the present application, the first positive electrode active material and the second positive electrode active material satisfy: Among them, n (Ni) is the molar amount of Ni element in the positive electrode, in mol; n (A′) is the molar amount of element A' in the positive electrode, in mol; n (P)is the molar amount of P element in the positive electrode, in mol. For example, The value of can be 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc., or can be a range consisting of any of the above values; for example, The value of can be 0.18, 0.2, 0.25, 0.3, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, etc., or can be a range consisting of any of the above values. Among them, the molar amount of each element in the positive electrode sheet can be obtained by ICP testing. For example, it can be carried out by the following operation: take about 0.4g (accurate to 0.0001g) of dry positive electrode sheet or 1g (accurate to 0.0001g) of wet positive electrode sheet in a 30ml digestion tank, retain one digestion tank without sample as a blank sample, move the digestion tank containing the positive electrode sample into the fume hood and add 12ml of reverse aqua regia. When adding reverse aqua regia, add it along the inner wall of the digestion tank so that the residual sample on the inner wall is washed into the bottom of the tank, and then install the top cover, insulation sleeve, gasket, microwave digestion device, nut in sequence, tighten the nut with a wrench, then turn on the microwave digester, insert the optical fiber sensor in the microwave digester into the bottom of the previously assembled digestion tank containing the sample, and place the digestion tank in the microwave digester in a balanced manner. Start digestion (digestion program: heat to 120℃ for 6 minutes and hold for 8 minutes, heat to 160℃ for 5 minutes and hold for 8 minutes, heat to 180℃ for 5 minutes and hold for 5 minutes). After the end, cool to room temperature and take out. Place the digestion tank in a fume hood, slowly unscrew the nut to release the air, remove the previously installed parts in turn, transfer the solution in the digestion tank to a 100ml volumetric flask through a funnel (filter paper is required), then rinse the digestion tank with ultrapure water, and transfer the rinse liquid to the volumetric flask, using 10ml of ultrapure water for each rinse. Shake the solution in the 100ml volumetric flask, use a pipette to take 1ml of the shaken solution and add it to another 100ml volumetric flask, then add ultrapure water to make up the volume (the total solution reaches 100ml), and finally use ICP-OES to test the sample solution. Among them, when preparing reverse aqua regia, you can pour 1000ml of ultrapure water into a 2500ml glass bottle, and then add 750ml of concentrated nitric acid and 250ml of concentrated hydrochloric acid in turn, stir evenly and set aside. The concentrated nitric acid can be purchased from the market as a concentrated nitric acid solution with a mass fraction of 68%, and the concentrated hydrochloric acid can be purchased from the market as a concentrated hydrochloric acid with a mass fraction of 68%, or hydrogen chloride gas and ultrapure water can be added to ultrapure water with a mass ratio of 68% and 32% respectively. After complete dissolution, the required concentrated hydrochloric acid can be obtained.

[0075] Among them, relative to the second positive electrode active material Li1+x M 3n Mn 1-y A′ y P 1-z E z O4, first positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g The specific capacity is higher and the conductivity is better, but the lattice volume change rate after lithium insertion and removal is low, which is not conducive to matching the volume expansion of the negative electrode after lithium insertion; further, the increase in the Ni content in the first positive electrode active material helps to improve the battery energy density, but is not conducive to the lattice shrinkage of the composite positive electrode, which will damage the cycle performance; doping other elements in the manganese position of the second positive electrode active material can improve its lattice shrinkage during lithium insertion and removal, and improve the cycle performance, but too much doping will damage the battery energy density. Selecting a suitable doping amount can simultaneously ensure the battery energy density and cycle performance. For example, as a specific example, when the manganese position contains both manganese and iron elements, a high manganese-iron ratio can increase the voltage platform, which is beneficial to improving the energy density of the battery, but when the manganese-iron ratio is too high, a large amount of trivalent manganese in the delithiation state may destroy the solid solution structure, reduce the specific capacity and cycle capacity retention rate of the material, resulting in poor cycle performance and affecting the life of the positive electrode. In this application, the Ni content in the positive electrode sheet is provided by the first positive electrode active material. By using and By satisfying the above-mentioned ranges respectively, not only can the first positive electrode active material and the second positive electrode active material have a suitable blending ratio, but also the second positive electrode active material can have a suitable manganese site doping ratio, thereby obtaining better cycle performance, and further enabling the secondary battery to have both higher energy density and better cycle performance.

[0076] Optionally, This can further make the first positive electrode active material and the second positive electrode active material have an appropriate blending ratio, and make the second positive electrode active material have better cycle performance, so that the secondary battery can further take into account both higher energy density and better cycle performance. When the first positive electrode active material does not contain the A' element, A' can be provided only by the second positive electrode active material. Meeting the above-given range conditions can further enable the secondary battery to have both higher energy density and better cycle performance.

[0077] In some embodiments of the present application, 0.001≤n (Ni) ≤0.0026, for example, n (Ni)It can be 0.0011, 0.0011, 0.0013, 0.0015, 0.0017, 0.0019, 0.0021, 0.0023, 0.0025, etc., or can be a range consisting of any of the above values, wherein, in the mixed positive electrode active material, the Ni element is provided by the first positive electrode active material, and the increase of the Ni element content in the first positive electrode active material is conducive to the improvement of the battery energy density, but is not conducive to the shrinkage of the composite positive electrode lattice, which will damage the cycle performance. In this application, by increasing the Ni element content in the positive electrode sheet to n (Ni) Satisfying the above range can further enable the secondary battery to have both higher energy density and better cycle performance. (Ni) ≤0.002, thereby further enabling the secondary battery to have both higher energy density and better cycle performance.

[0078] In some embodiments of the present application, 0.00007≤n (A′) ≤0.00075, for example, n (A′) It can be 0.0001, 0.00015, 0.0002, 0.00025, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, etc., or can be a range consisting of any of the above values. Doping other elements in the manganese position of the second positive electrode active material can improve its lattice shrinkage during the lithium insertion and extraction process and improve the cycle performance, but excessive doping will damage the battery energy density. In this application, by making the content of A' element in the positive electrode sheet n (A′) Satisfying the above range can further enable the secondary battery to have both higher energy density and better cycle performance. (A′) ≤0.00032, thereby further enabling the secondary battery to have both higher energy density and better cycle performance.

[0079] In some embodiments of the present application, depending on the type of secondary battery, the battery housing may be an aluminum-plastic film or a metal housing assembly, etc. The metal housing assembly may further include a square housing assembly and a cylindrical housing assembly. When the battery housing is a metal housing assembly, it generally includes a housing having an opening on at least one side and a cover for sealing the opening. The composition of the negative electrode sheet and the specific material or type of the separator may adopt materials or types commonly used in the art, and the composition of the electrolyte may also adopt a common composition commonly used in the art. The selection of the positive active material in the positive electrode sheet has been described in detail in the previous section and will not be repeated here. Regarding the selection of the binder, conductive agent, and thickness of the positive active material layer, those skilled in the art may also flexibly make their own choices based on actual needs.

[0080] In some embodiments of the present application, the secondary battery can be either a laminated battery or a wound battery. The wound battery can be either a square battery or a cylindrical battery. Optionally, the battery can be a cylindrical battery. Depending on the battery type, the positive electrode sheet, the negative electrode sheet, and the separator can be stacked to form a laminate unit, or can be stacked and then wound to form a wound body.

[0081] In some embodiments of the present application, the secondary battery may be a single cell or a battery module assembled from cells. A battery module may include multiple cells, the specific number of which may be adjusted based on the application and capacity of the battery module. Furthermore, the battery module may also include a packaging assembly having a storage space, which may include a bottom plate, side plates, and a cover plate.

[0082] In some embodiments of the present application, the above-mentioned battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0083] In addition, the present application also provides an electrical device, which includes: the secondary battery of the first aspect of the present application.

[0084] The secondary battery, such as a battery cell, a battery module or a battery pack, can be used as both a power source and an energy storage unit for the electrical device. The electrical device may include, but is not limited to, a mobile device (e.g., a mobile phone, a laptop computer), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, and an energy storage system. As a specific example, the electrical device may be a vehicle.

[0085] The electrical device can select the specific type of battery according to its usage requirements, such as battery cells, battery modules or battery packs.

[0086] As an example, the electric device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery pack or battery module may be used.

[0087] As another example, the electrical device may be a mobile phone, a tablet computer, or a laptop computer. The electrical device is generally required to be lightweight and thin, and may use a battery cell as a power source.

[0088] Below, the embodiment of the present application is described. The embodiment described below is exemplary, is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiment, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0089] Preparation and testing methods of secondary batteries:

[0090] 1. Soft-pack laminated battery:

[0091] ① Preparation of positive electrode sheet:

[0092] The positive electrode active material, polyvinylidene fluoride (PVDF), and conductive carbon are added to a certain amount of N-methylpyrrolidone (NMP) with a mass ratio of positive electrode active material: polyvinylidene fluoride: conductive carbon of 90:5:5. The mixture is stirred in a drying room to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·s. The slurry is then coated on aluminum foil and dried to form a positive electrode sheet.

[0093] ② Preparation of negative electrode sheet:

[0094] Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon were added to a certain amount of deionized water. The mass ratio of graphite: sodium carboxymethyl cellulose: styrene-butadiene rubber: conductive carbon was 90:2:3:5. The mixture was stirred to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·s. The slurry was then coated on copper foil and dried to form a negative electrode sheet.

[0095] ③ Preparation of soft-pack laminated batteries:

[0096] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are made into corresponding battery cells according to a Z-shaped stacking structure, and the battery cells are vacuum dried at 90°C for 12 hours, and then the positive and negative electrode tabs are ultrasonically welded. The positive electrode uses an aluminum tab and the negative electrode uses a nickel tab. The positive and negative electrode tabs are located on the same side of the battery cell. The battery cell after the tab welding is placed in an aluminum-plastic film of appropriate size for top-side packaging. The conventional packaging temperature is 145°C, and the electrolyte is injected (the electrolyte is 1 mol / L LiPF6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1) + 5wt.% fluoroethylene carbonate (FEC)), let it stand, form, age, exhaust, seal, and capacity test to obtain the prepared soft-pack laminated battery.

[0097] 2. Perform a cycle test on the soft-pack laminated battery prepared in (a) at 25°C:

[0098] The prepared soft-pack laminated battery was charged to 4.4V at 0.5C0 at 2.5-4.4V in a constant temperature environment of 25°C, then charged at a constant voltage at 4.4V to a current ≤ 0.05C0, allowed to stand for 5 minutes, and then discharged to 2.5V at 1C0. The capacity was recorded as C n (n=1,2,3……), repeat the above operation, the capacity retention rate is calculated according to C n / C3 ratio calculation, when C n / C3×100%=80%, extract the corresponding number of cycles as the evaluation index of the cycle capacity; after the cycle test, disassemble the negative electrode in a dry room or glove box, wash the residual lithium salt crystals on the surface of the electrode with the main solvent of the electrolyte of the above battery, and take a 1×2 cm 2 The sample is transferred to a vacuum transfer device or in an inert atmosphere, and then cut into sections using an argon ion beam milling (CP) device at low temperature. After cutting, the sample is attached to the cross-section sample stage with conductive tape and transferred to the SEM vacuum chamber for observation to obtain the sample cross-sectional morphology. Observe whether lithium is deposited at the negative electrode interface.

[0099] Example 1

[0100] In soft-pack laminated batteries:

[0101] (i) Positive electrode

[0102] The number of layers N1 of the positive electrode sheet is 15; the thickness d of the single-layer positive electrode sheet is 正极 The active material layer compaction density of the positive electrode is 3.10g / cm 3 The first positive electrode active material is NCM523; the Dv50 particle size of the first positive electrode active material is 4.1 μm; the second positive electrode active material is LiMn 0.6 Fe 0.4 PO4, the Dv50 particle size of the second positive electrode active material is 0.81 μm; the first positive electrode active material and the second positive electrode active material meet the following requirements: Wherein A' is Fe element.

[0103] (ii) Negative electrode

[0104] The number of negative electrode sheets N2 is 16, and the thickness of a single negative electrode sheet is d 负极 The active material layer of the negative electrode sheet has a compaction density of 1.70 g / cm 3 .

[0105] (iii) Diaphragm

[0106] The number of diaphragm layers N3 is 16, and the thickness of a single diaphragm is d 隔膜 0.011mm;

[0107] (iv) Inner thickness of the battery housing d 壳体 4.5mm;

[0108] (vi) The filling coefficient of the secondary battery is 2.73 g / Ah;

[0109] (v) The group margin is:

[0110] Examples 2 to 5 and Comparative Examples 1 to 3

[0111] The differences between Examples 2 to 5 and Comparative Examples 1 to 2 and Example 1 are: the inner cavity thickness of the battery shell is different, and the group margin of the secondary battery is different, as shown in Table 1 for details.

[0112] The difference between Comparative Example 3 and Example 1 is that the composition of the positive electrode active material is different. Comparative Example 3 does not contain the second positive electrode active material, as shown in Table 1 for details.

[0113] Examples 6 to 13

[0114] The difference between Examples 6 to 13 and Example 1 is that the filling coefficients of the secondary batteries are different, as shown in Table 1 for details.

[0115] Examples 14-15

[0116] The difference between Examples 14 to 15 and Example 1 is that the composition of the second positive electrode active material is different, as shown in Table 1 for details.

[0117] Examples 16 to 20

[0118] The difference between Examples 16 to 20 and Example 1 is that: in the first positive electrode active material and the second positive electrode active material, The values ​​of are different (A′ is Fe element), see Table 1 for details.

[0119] Examples 21 to 24

[0120] The difference between Examples 21 to 24 and Example 1 is that the Dv50 particle size of the first positive electrode active material is different, see Table 1 for details.

[0121] Examples 25 to 28

[0122] The difference between Examples 25 to 28 and Example 1 is that the Dv50 particle size of the second positive electrode active material is different, see Table 1 for details.

[0123] The secondary batteries assembled in Examples 1 to 28 and Comparative Examples 1 to 3 were subjected to cycle performance tests. The test results are shown in Table 1.

[0124] Table 1 Differences between Examples 1 to 28 and Comparative Examples 1 to 3 and related test results

[0125] Results and Conclusions:

[0126] It can be seen from the examples and comparative examples that the battery design scheme of the present application can improve the cycle performance and safety performance of high group margin batteries. Specifically, it can be seen from Examples 1 to 5 and Comparative Examples 1 to 3 that by blending the nickel-cobalt-manganese ternary positive electrode active material with the lithium iron manganese phosphate positive electrode active material and controlling the group margin of the battery within the range of 0.9 to 0.95, the number of cycles in which the battery capacity retention rate is reduced to 80% can be increased to more than 1000, and there is no lithium plating problem. Furthermore, it can be seen from the data in Table 1 that after blending the nickel-cobalt-manganese ternary positive electrode active material with the lithium iron manganese phosphate positive electrode active material, the group margin of the battery will also affect the cycle performance and safety of the battery. Too high or too low a group margin is not conducive to improving the battery cycle performance, and too high a group margin will also cause lithium plating problems, affecting the safety of the battery. It can be selected from 0.91 to 0.94. In combination with Examples 1, 6 to 13, it can be seen that for the battery design of the above embodiments of the present application, the filling coefficient will also affect the cycle performance and safety of the battery to a certain extent. As the filling coefficient increases, its range can be selected as 2.5g / Ah to 3.0g / Ah, and then as 2.62g / Ah to 2.90g / Ah. In combination with Examples 1, 14 to 20, it can be seen that for the battery design of the above-mentioned embodiments of the present application, the composition of the second positive electrode active material and the molar ratio of the A′ element to the Ni element will also affect the cycle performance and safety of the battery to a certain extent. The main reason is that when the second positive electrode active material changes, the improvement effect of the battery cycle performance and safety performance after it is mixed with the nickel-cobalt-manganese ternary positive electrode active material may also change. The molar ratio of the A′ element to the Ni element limits the mixing ratio of the second positive electrode active material and the nickel-cobalt-manganese ternary positive electrode active material to a certain extent. The mixing ratio of the two is different, and the improvement effect on the battery cycle performance and safety performance may also change. Among them, the molar ratio of the A′ element to the Ni element can be selected as 0.02 to 1.5, and then as 0.02 to 0.2. In combination with Examples 1, 21 to 28, it can be seen that for the battery design of the above-mentioned embodiments of the present application, the particle size of the first positive electrode active material and the particle size of the second positive electrode active material will also affect the cycle performance and safety of the battery to a certain extent. The main reason is that the change in the particle size of the two will affect the active sites, compaction density and diffusion path of active ions of the positive electrode active material, among which the Dv50 particle size of the first positive electrode active material can be selected as 2.1μm~6.3μm, and the Dv50 particle size of the second positive electrode active material can be selected as 0.25μm~1.49μm.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A secondary battery, wherein: include: A battery case and a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte placed in the battery case, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, wherein: the positive electrode sheet comprises a positive electrode active material layer, the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material, The first positive electrode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, etc., and R′ includes one or more elements selected from N, F, S, Cl, etc.; The second positive electrode active material includes Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, wherein -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤1, 0≤z≤0.100, M3 includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, A′ includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge, and E includes one or more elements selected from the group consisting of B, Si, N, S, F, Cl, and Br; The secondary battery meets the following requirements: Among them, d 正极 is the thickness of the single-layer positive electrode sheet, in mm; d 负极 is the thickness of the negative electrode sheet of a single layer, in mm; d 隔膜 is the thickness of the single-layer diaphragm, in mm; d 壳体 is the inner cavity thickness of the battery shell, in mm; N1 is the number of layers of the positive electrode sheets in the battery shell; N2 is the number of layers of the negative electrode sheets in the battery shell; N3 is the number of layers of the diaphragm in the battery shell.

2. The secondary battery according to claim 1, wherein The second positive electrode active material includes a positive electrode active material that satisfies at least one of the following conditions: (i) y=1, n=0, the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' is Fe, or A' is Fe and one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge; (ii) 0.001≤y≤0.500, n=0, the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4; (iii) 0.001≤y≤0.500, 0.9≤n≤1.1, and the second positive electrode active material is Li 1+x M 3n Mn 1-y A′ y P 1- z E z O4.

3. The secondary battery according to claim 1 or 2, wherein:

4. The secondary battery according to any one of claims 1 to 3, wherein 0.11mm≤d 正极 ≤0.16mm, optionally, 0.12mm≤d 正极 ≤0.14mm; 0.15mm≤d 负极 ≤0.20mm, optionally, 0.16mm≤d 负极 ≤0.18mm.

5. The secondary battery according to any one of claims 1 to 4, wherein 0.009mm≤d 隔膜 ≤0.014mm, optionally, 0.0011mm≤d 隔膜 ≤0.012mm.

6. The secondary battery according to any one of claims 1 to 5, wherein When the positive electrode sheet is in a fully de-lithiated state, the average lattice volume shrinkage rate of the positive electrode active material is not less than 2.7%.

7. The secondary battery according to any one of claims 1 to 6, wherein When the positive electrode sheet is in a fully de-lithiated state, the lattice volume shrinkage rate of the second positive electrode active material is 2.7% to 6.9%.

8. The secondary battery according to any one of claims 1 to 7, wherein When the positive electrode sheet is in a fully de-lithiated state, the average lattice volume shrinkage rate of the positive electrode active material is 2.7% to 4.2%.

9. The secondary battery according to any one of claims 1 to 8, wherein The compacted density of the active material layer of the positive electrode sheet is 3.10 g / cm 3 ~3.50g / cm 3 , optional 3.15g / cm 3 ~3.40g / cm 3 , and 3.15g / cm 3 ~3.35g / cm 3 .

10. The secondary battery according to any one of claims 1 to 9, wherein The compaction density of the active material layer of the negative electrode sheet is 1.6 g / cm 3 ~1.70g / cm 3 , optional 1.64g / cm 3 ~1.69g / cm 3 .

11. The secondary battery according to any one of claims 1 to 10, wherein The liquid injection coefficient of the secondary battery is 2.5 g / Ah to 3.0 g / Ah, and can be 2.62 g / Ah to 2.90 g / Ah, and can be 2.70 g / Ah to 2.90 g / Ah.

12. The secondary battery according to any one of claims 1 to 11, wherein A first coating layer is provided on the surface of the first positive electrode active material. Optionally, the first coating layer includes one or more elements selected from the group consisting of Ti, Al, B, Nb, Zr, Si and W.

13. The secondary battery according to claim 12, wherein: The thickness of the first coating layer is 20 nm to 150 nm.

14. The secondary battery according to any one of claims 1 to 13, wherein A second coating layer is provided on the surface of the second positive electrode active material. Optionally, the second coating layer includes at least one of pyrophosphate, phosphate and carbon.

15. The secondary battery according to claim 14, wherein The thickness of the second coating layer is 10 nm to 50 nm.

16. The secondary battery according to any one of claims 1 to 15, wherein The Dv50 particle size of the first positive electrode active material is 2.1 μm to 6.3 μm, and can be 3.5 μm to 4.9 μm; and / or, The Dv50 particle size of the second positive electrode active material is 0.25 μm to 1.49 μm, and can be optionally 0.5 μm to 0.9 μm.

17. The secondary battery according to any one of claims 1 to 16, wherein In the second positive electrode active material, E includes one or more elements selected from the group consisting of B, Si, N and S.

18. The secondary battery according to any one of claims 1 to 17, wherein In the second positive electrode active material, A' includes one or more elements selected from the group consisting of Fe, Ti, V and Mg.

19. The secondary battery according to any one of claims 1 to 18, wherein The second positive electrode active material includes a positive electrode active material that satisfies at least one of the following conditions: (i) y=1, n=0, the second positive electrode active material is Li 1+x A′P 1-z E z O4, A' is Fe, or A' includes Fe and one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb, and Ge; (ii) 0.001≤y≤0.500, n=0, the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4.

20. The secondary battery according to any one of claims 1 to 19, wherein The first positive electrode active material and the second positive electrode active material satisfy: in, n (Ni) is the molar amount of Ni in the positive electrode sheet, in mol; n (A′) is the molar amount of A' in the positive electrode sheet, in mol; n (P) is the molar amount of P in the positive electrode sheet, in mol.

21. The secondary battery according to claim 20, wherein 22. The secondary battery according to claim 20 or 21, wherein 23. The secondary battery according to any one of claims 20 to 22, wherein 0.001≤n (Ni) ≤0.0026, optionally, 0.0014≤n (Ni) ≤0.002; 0.00007≤n (A′) ≤0.00075, optionally, 0.0001≤n (A′) ≤0.00032.

24. An electrical device, wherein: A secondary battery comprising the secondary battery according to any one of claims 1 to 23.

Citation Information

Cited By

  • Lithium manganese iron phosphate material, preparation method thereof, battery monomer, battery device and power utilization device

    CN120914318A

  • Positive pole piece, battery, battery pack and electric device

    CN121366869A